TRADISI MUNGGAH MOLO DI PEKALONGAN - ULA, MIFTAHUL (Fakultas Ilmu Budaya Universitas Diponegoro, 2015)
This study will attempt to uncover the tradition of munggah molo in Pekalongan to explore its forms of language; meanings embodied in symbols of munggah molo tradition; and the relationship between the function symbols in munggah molo tradition with social values and religious in Pekalongan.This study uses anthropology of linguistic approach looking through the prism of the core concepts of anthropology, culture, and look for the hidden meaning behind the use or misuse of language in different forms, namely registers and style.In the tradition of munggah molo performed by the Java community in Pekalongan are forms of language in the form of a special lexicon commonly used in munggah molo tradition. Likewise, in this tradition contain the symbolic languages that contain the values of life like munggah, molo, blandar, uwat-uwat, bengking, Gendero, kembang setaman (flower setaman), banan Sepet, basin, money nickels, canticles, coconut, umbrellas, golden spikes, rays, juwadah pasar, and so forth.The symbols contained in molo munggah tradition means and intent that is hope. These symbolic meanings in some ways, a myth or public trust Pekalongan in understanding life. It occurs in hereditary and implemented to date in spite of the shift even a change in the procession and implementation.The tradition of munggah molo in Pekalongan has a very important social function, especially in establishing social harmony in the society of Pekalongan. This harmony is not only applied for the Java community alone, but also the impact of this harmony can also be perceived by others as Chinese and Arabic ethnic.